2017
DOI: 10.1016/j.cobeha.2016.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Tripping up addiction: the use of psychedelic drugs in the treatment of problematic drug and alcohol use

Abstract:  Psychedelic drugs may have their therapeutic qualities due to anti-depressant effects, stimulating neuroplasticity and long-term psychological changes.3 Abstract Psychedelic drugs have been used as treatments in indigenous cultures for thousands of years. Yet, due to their legal status, there has been limited scientific research into the therapeutic potential of these compounds for psychiatric disorders. In the absence of other effective treatments however, researchers have begun again to systematically inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 53 publications
0
27
0
Order By: Relevance
“…The observed ability of psychedelics to facilitate self-exploration through the enhancement self-awareness and reliving of autobiographic memories has been proposed as a key mechanism in early psychotherapeutic research with LSD (Vollenweider & Kometer, 2010). The question raised by this relationship, that is, what functional role self-medication might play in psychedelic use, stands out as a particularly relevant one in a time where psychedelic compounds are increasingly being reconsidered as psychotherapeutic tools (Carhart-Harris & Goodwin, 2017; Morgan, McAndrew, Stevens, Nutt, & Lawn, 2017; Tupper, Wood, Yensen, & Johnson, 2015) and should be explored in future research.…”
Section: Discussionmentioning
confidence: 99%
“…The observed ability of psychedelics to facilitate self-exploration through the enhancement self-awareness and reliving of autobiographic memories has been proposed as a key mechanism in early psychotherapeutic research with LSD (Vollenweider & Kometer, 2010). The question raised by this relationship, that is, what functional role self-medication might play in psychedelic use, stands out as a particularly relevant one in a time where psychedelic compounds are increasingly being reconsidered as psychotherapeutic tools (Carhart-Harris & Goodwin, 2017; Morgan, McAndrew, Stevens, Nutt, & Lawn, 2017; Tupper, Wood, Yensen, & Johnson, 2015) and should be explored in future research.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical research suggests that CSP-assisted therapyin which patients take a relatively mild or a large dose of psychedelics under the supervision of a therapist -can help to alleviate psychological distress and different mental health problems (see Carhart-Harris and Goodwin 2017 for an overview), including distress associated with life-threatening illness (Griffiths et al 2016); various forms of addiction including alcoholism and tobacco addiction (Bogenschutz et al 2015;Johnson et al 2017;Morgan et al 2017), and recurrent and treatment-resistant anxiety and depression disorders (Carhart-Harris et al 2018a;Palhano-Fontes et al 2019). Such effects on mental health are likely mediated by the extent to which participants have mystical-type and self-transcendent experiences during their CSP 'trip' (Bogenschutz et al 2015;Griffiths et al 2016;Johnson et al 2017;Roseman et al 2018;Ross et al 2016).…”
Section: Psychedelic Experiences: Mysticism Awe and Ego Dissolutionmentioning
confidence: 99%
“…In recent years, there has been a steady increase in research suggesting that certain drugs typically classified as recreational drugs may be used effectively in mental health research and care, in particular for depression (Carhart-Harris et al 2018a;Singh et al 2016), post-traumatic stress disorder (Mithoefer et al 2018), and substance addiction (Morgan et al 2017). Psychedelic drugs in particular hold a great potential not only for treating a wide range of clinical disorders (Carhart-Harris and Goodwin 2017), but also for fostering prosocial behaviour and helping to address non-clinical but problematic interpersonal styles and behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the past decade, there has been a resurgence of interest in psychedelics among medical researchers. Recent clinical trials have suggested that these plants may be effective treatments for smoking cessation (Johnson et al, 2016), anxiety, depression and post-traumatic stress disorder (PTSD) (Carhart-Harris et al, 2016; Griffiths, 2010, Grob et al, 2011; Ross et al, 2016), addiction (Bogenschultz et al, 2015; Griffiths, 2010; Loizaga-Velder & Verres, 2014; Morgan et al, 2017), obsessive-compulsive disorder (OCD) (Moreno et al, 2006) and cluster headaches (Davenport, 2016; Sewell et al, 2006). MDMA was approved by the Federal Drug Administration (FDA) for Phase III clinical trials in 2016 and psilocybin is currently being considered for Phase III clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…The potential impact of plant medicines on physical health has been largely unexplored. Clinical trials to date have not made definitive conclusions on the potential mental, spiritual and physical benefits of plant medicine use, although studies of ayahuasca and psilocybin have shown promising results for depression, anxiety, PTSD, addiction, OCD, and headaches (Bogenschultz et al, 2015; Carhart-Harris et al, 2016; Davenport, 2016; Griffiths, 2010, Grob et al, 2011; Johnson et al, 2016; Loizaga-Velder & Verres, 2014; Moreno et al, 2006; Morgan et al, 2017; Ross et al, 2016). Significant gaps in the literature exist regarding the risks and possible benefits of these plants across the spectrum of health.…”
Section: Introductionmentioning
confidence: 99%